Outbreak or illusion: consequences of 'improved' diagnostics for gonorrhoea. (June 2017) - Bennett, Amy; Jeffery, Katie; O'Neill, Eunan; Sherrard, Jackie
The sexual health service in Oxford introduced gonorrhoea nucleic amplification acid testing using the BD Viper XTR™ System. For practical reasons, a confirmatory nucleic amplification acid testing using a different platform was not used initially. Following the introduction of nucleic amplification acid testing, the rates of gonorrhoea increased threefold. Concerns were raised that this increase represented an outbreak. A retrospective review of cases over six months suggested that there may have been a number of false-positive results. A prospective study was then undertaken over six months, where all gonorrhoea positive samples were sent for confirmatory testing. This evaluation of all gonorrhoea cases in an English county found that the overall presumptive false-positive rates for gonorrhoea nucleic amplification acid testing using BD Viper XTR™ in our population are significant at 27% of female samples, 13.2% of heterosexual male samples, 3.5% of anogenital multiple site men who have sex with men samples and 62.8% of pharyngeal only men who have sex with men samples. The data demonstrate the need for confirmatory testing using a second nucleic acid target, as per BASHH/Public Health England guidelines, especially in low-prevalence settings and extragenital sites, due to cross-reactivity with commensal Neisseria species and low positive predictive values.